Parental awareness of the nutritional intake to their children's growth - Siti Zaharah Ibrahim (2022)
Nowadays, several reports from international bodies on nutritional requirements are alarming. Based on a report by the World Health Organization found that 17.7 percent of children and adolescents aged 5 to 19 years old in Malaysia have stunted growth. Besides, many parents are not aware of nutrition intake in providing food to their children. Therefore, this study aims to determine parental awareness of the nutritional intake to their children's growth. The independent variables in this study are knowledge, attitude, practices, perceived behaviour control, and subjective norm while the dependent variable is parent awareness of nutrient intake of their children. Quantitative research forms were used and questionnaires were adapted based on the KAP Model and the theory of planned behaviour (TPB). Non-probability sampling was used using purposive sampling involving 150 parents who have children from age five until twelve years old. SPSS version 21.0 was used to analyze the data using reliability tests, normality tests, descriptive statistics, and correlation. Based on the results of this study found that all the variable has a high mean score. The results of the study also showed that there was a significant relationship between knowledge, attitudes, practices, subjective norms, and perceived behavioural control with parental awareness of nutrient intake in children. Hopefully, this study raises the awareness of parents about the importance of providing a balanced and healthy diet for the children’s growth.